2015
DOI: 10.1001/jamadermatol.2014.4728
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Histologic, and Molecular Analysis of Differences Between Erythematotelangiectatic Rosacea and Telangiectatic Photoaging

Abstract: Telangiectatic photoaging is characterized by less transient and nontransient erythema, a more lateral distribution of erythema and telangiectasia, less neurogenic mast cell activation, and less MMP-mediated matrix remodeling than ETR. These data demonstrate that TP is a distinct clinical entity from ETR that can be distinguished on the basis of clinical, histologic, and gene expression findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
68
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 34 publications
2
68
1
1
Order By: Relevance
“…1 Moreover, photodistributed, mostly vasodilator drug-related telangiectasia underscores the potential role for actinic exposure in the pathogenesis of telangiectasia. 6 Yano et al 7 and Kajiya et al, 8 in exploring the mechanisms of acute UV-B-induced angiogenesis and photodamage in human skin, demonstrated the consequent epidermal hyperplasia, infiltration of elastin-producing neutrophils, and elastin fiber damage, along with a significant increase in both vascular density and vessel size, features consistent with the proposed pathogenesis of ETR 1 as well as the cutaneous signs of telangiectatic photoaging (TP), as described by Helfrich et al 9 There are now plausible molecular links for clinically well-recognized rosacea triggers, including actinic damage, with the proposed inflammatory vascular pathogenesis of rosacea, beginning with ETR. 1 However, not everyone agrees that rosacea begins with ETR or that ETR is even a subtype of rosacea.…”
supporting
confidence: 62%
See 3 more Smart Citations
“…1 Moreover, photodistributed, mostly vasodilator drug-related telangiectasia underscores the potential role for actinic exposure in the pathogenesis of telangiectasia. 6 Yano et al 7 and Kajiya et al, 8 in exploring the mechanisms of acute UV-B-induced angiogenesis and photodamage in human skin, demonstrated the consequent epidermal hyperplasia, infiltration of elastin-producing neutrophils, and elastin fiber damage, along with a significant increase in both vascular density and vessel size, features consistent with the proposed pathogenesis of ETR 1 as well as the cutaneous signs of telangiectatic photoaging (TP), as described by Helfrich et al 9 There are now plausible molecular links for clinically well-recognized rosacea triggers, including actinic damage, with the proposed inflammatory vascular pathogenesis of rosacea, beginning with ETR. 1 However, not everyone agrees that rosacea begins with ETR or that ETR is even a subtype of rosacea.…”
supporting
confidence: 62%
“…1 However, not everyone agrees that rosacea begins with ETR or that ETR is even a subtype of rosacea. Helfrich et al 9 remind us that ETR is probably the most disputed subtype of rosacea, with some authors arguing that it is merely photodamage or, at least, difficult to distinguish from photodamage. This is a curious twist given that rosacea was first recognized as a distinct facial dermatosis separate from common acne (acne vulgaris) by virtue of its rosy hue (acne rosacea).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, treatment with a brimonidine gel was as- and matrix metalloproteinase-9 (MMP-9), which are important in the pathogenesis of rosacea. [7,8] Furthermore, the number of MCs is increased in skin lesions of patients with rosacea, and inhibition of this increased MC activity has been suggested as a potential treatment for rosacea. [9] Interestingly, we found an increase in mRnA levels of chymase and tryptase in the MCs in mouse skin injected with LL-37, which was consistent with previous study by Muto et al [4] In addition, Muto et al suggested that MCs play an important role in the development of rosacea by demonstrating that MC stabilizers improve rosacea phenotype by decreasing MMP activity and MC proteases (chymase and tryptase) in both rosacea-induced mouse model and patients with rosacea.…”
Section: Resultsmentioning
confidence: 99%